2017
DOI: 10.3390/su9111931
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Managerial Efficiency of Educational Tourism in Agriculture: Case of Dairy Farms in Japan

Abstract: Many rural areas face difficulty in how to motivate farmers to embark on diversified activities, such as tourism, while raising managerial efficiency. Thus, this paper conceptually and empirically evaluated how a farmer's identity correlates with managerial efficiency since the connection between the two has not been explored fully. We have addressed this issue through examining farmers' efforts in providing an emerging new educational tourism service by focusing on the Educational Dairy Farms in Japan. Concep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 72 publications
(69 reference statements)
3
26
0
Order By: Relevance
“…This is in line with the approach of Ohe Y. [91] who has proven that rural tourism can be an important actor in education.…”
Section: Wine Tourism Development and Sustainabilitysupporting
confidence: 86%
“…This is in line with the approach of Ohe Y. [91] who has proven that rural tourism can be an important actor in education.…”
Section: Wine Tourism Development and Sustainabilitysupporting
confidence: 86%
“…Although understudied, scholars suggest that agritourism may also serve as a way to engage consumers in ways that further contribute to sustainable LFS. Several studies have consistently shown that agritourism operators are strongly motivated to educate visitors about agricultural systems (McGehee, Kim, and Jennings 2007; Ohe 2017, 2018; Tew and Barbieri 2012). Some consumer studies, although to a lesser extent, indicated that visitors are motivated to engage in agritourism to learn about agriculture and local foods (Xu et al 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, these studies have prevalently concerned traditional accommodation (e.g., hotels) rather than agritourism or, more generally, rural tourism. Recently, Ohe [41] estimated efficiency in Japanese dairy farms that provide educational tourism. Using a DEA approach, the author evaluated the managerial efficiency of educational dairy farms taking into account both provision of milk produced and educational tourism.…”
Section: Of 15mentioning
confidence: 99%
“…Basically, this occurs because the term "rural tourism" has taken over in recent decades. A common opinion is, however, that agritourism and rural tourism are intended to be different concepts, with agritourism representing a sub-sample of rural tourism [33,41].…”
Section: Agritourism Definition and Some Data On Italian Agritourismmentioning
confidence: 99%